The French Connection: Charles Clermont-Ganneau and the Antiquities Trade Network in the Late Ottoman Levant - Preß, Michael (Journal of ancient Judaism, 2023)
Charles Clermont-Ganneau is widely recognized by scholars for his contributions to the archaeology, epigraphy, and historical geography of Israel/Palestine and the broader Middle East. But Clermont-Ganneau was also a major contributor to antiquities trade networks between the Levant and France in the Late Ottoman period. For a period of more than 35 years, he served variously as finder, agent, consultant, buyer, and dealer of ancient artifacts of all types. This article looks at Clermont-Ganneau’s involvement in antiquities trafficking and how it was intertwined with his scholarly career. A close study of his activities suggests that Clermont-Ganneau’s career is a paradigmatic example of academic reliance on the antiquities trade.